Consumer behavior of Islamic bank customers at Bank Rakyat Jelapang Branch, Ipoh, Malaysia / Nor Fatin Amirah Abd Razak - Abd Razak, Nor Fatin Amirah (Faculty of Business and Management, 2015)
This study investigates the consumer behaviour of Islamic bank customers at Bank Rakyat Jelapang Branch, Ipoh, Malaysia. It includes determination of factors that influence consumer behavior among customers. Several factors were established which were customer awareness, customer satisfaction, and bank selection criteria. The data was collected from a sample of 100 customers of Bank Rakyat Jelapang through questionnaire. The data was analysed by using SPSS version 20.0. The data analysis such as descriptive, reliability and regression were used to achieve the objective of this research. It was found that the high level of Consumer behavior of Islamic bank customer at Bank Rakyat Jelapang. All of the determinants or factor had the significant relationship toward consumer behavior of customers and most significant factor that influence consumer behavior of customers was bank selection criteria.